Digital marketing strategies in healthcare services: literature review - Berliana Oktavia Setyawati; Ernawaty (Universitas 'Aisyiyah Yogyakarta, 2024)
The impact of technological advancements has led to a shift in the paradigm of marketing healthcare services. Marketing in the digital era is highly complex as market conditions can change rapidly beyond providers' control. Digital marketing offers several advantages compared to conventional marketing. Healthcare service providers can integrate digital marketing into their healthcare marketing strategies. This research aims to identify digital marketing strategies in healthcare services. The research method used is a literature review. The researcher used the PRISMA protocol as a guiding framework to ensure systematic and transparent article selection. The databases used are Science Direct and PubMed. After undergoing a thorough screening process, eight articles that met all the eligibility criteria were finally selected. The review identifies several effective digital marketing strategies, including email marketing, social media marketing, and website marketing with SEO, all of which enhance patient engagement and increase the visibility of healthcare services. Additionally, digital twin technology personalizes patient experiences through real-time data, improving service recommendations and operational efficiency. Together, these strategies boost the effectiveness of healthcare marketing in the digital era, though data security and patient privacy must be carefully managed.